Comparison of active calf muscle stretching versus ankle mobilisation on low back pain and lumbar flexibility in pronated foot subjects - Vadivelan, K.; Poyyamozhi, J. S.; Dinesh Kumar, G.; Rajan Rushender, C. (International Journal Of Community Medicine And Public Health, 2017)
Background: Low back pain is the common symptom of the lumbar region that more than 80 percent of people experience in their lifetime. Methods: Quasi-experimental study was conducted with three intervention groups. Ankle mobilization (Group I), Active stretching of calf muscle (Group 2), No Intervention (Group 3). This study was carried out in the Department of Physiotherapy at SRM University, Chennai. 21 subjects were included in the study, with 7 subjects in each group. Results: Median age was found to be 20 (19–21), 19 (18–20) and 21 (20–22) in group 1, group 2 and group 3 respectively and no significant difference was seen between the groups, p value 0.11) There was a significant improvement seen in visual analogue scale, in both the intervention groups before and after intervention. The median and IQR for ankle mobilization group pre and post intervention was 6 (IQR, 5–6) and 4 (IQR, 3–5) respectively, with a p value <0.01. Conclusions: Overall results have shown that both the intervention groups have similar effects in reducing lower back pain and improving lumbar flexion, compared to the control group.